On the dynamic absorber for self- excited system - Dao, Nguyen Van (Vietnam Journal of Mechanics, 1982)
In this article it is shown that not only the << relative >> friction between basic mass and absorber as proposed in [ 1-3 ] but the << absolute >> friction between absorber and foundation has decisive role in the extinguishing of self – excited oscillation of the basic mass.